Neuromuscular disorders in acute leukemia and lymphoma treatment - E. A. Politova; N. N. Zavadenko (Онкогематология, 2014)
Different mechanisms of neuromuscular complications, their clinical presentation, methods of diagnosis, prognosis and treatment options are presented. The material is presented according to the level of nervous system damage, with inclusion of different clinical entities. Authors reviewed a wide range of disease – disease of the spinal cord, peripheral nerves and plexus, neuromuscular junction and muscle – as a result of chemotherapy and radiation therapy. Systemic effects of drugs on peripheral nervous system, various departments of which can be simultaneously involved in the pathological process, were also highlighted.